Judgment at Nuremberg: Foreword to the Symposium - Leila Nadya Sadat (Washington University Global Studies Law Review, 2007)
The Nuremberg Judgment, and the trial that preceded it, have been the subject of many academic conferences over the years, and yet it is difficult to overstate their importance. As an historical matter, Nuremberg represented the first modern, successful international war crimes trial. The IMT was created by international treaty, and although it suffered from the stigma that the victors sat in judgment of the vanquished, the precedent it established was subsequently internationalized and embraced by the fledgling United Nations. The law of the UN Charter, as enshrined in the IMT’s judgment and later codified by the International Law Commission, laid the foundation for the now-burgeoning discipline of international criminal law, and human rights law as well. In holding that “crimes are committed by men, not by abstract entities,” the IMT broke new ground, finding that individuals, not just States, could be subjects of international law and acquire duties thereunder. The corollary was that individuals are endowed with rights, as well.
Keywords: War crimes; International criminal law; Nuremberg War Crime Trials; Nuremberg; Germany; 1945-1949